Urusei Yatsura. Vol. 4 - Takahashi, Rumiko, 1957- (VIZ Media, LLC, 2019)
"The hilarious manga classic featuring beautiful space alien princess Lum! Beautiful space alien princess Lum invades Earth on her UFO, and unlucky Ataru Moroboshi's world gets turned upside down! Will Lum become Earth's electrifying new leader? Or will Ataru somehow miraculously save Earth from space alien onslaught? Lum's childhood friend Ran continues to cause trouble with her kisses, but that's the least of Ataru's worries! Ten, Lum's little cousin, arrives at the Moroboshi household, creating chaos at every turn. A miniature gentleman and self-proclaimed playboy, Ten loves Lum but hates Ataru. How will Ataru contend with this new fire-breathing nemesis?"--Provided by publisher.